MANAJEMEN PEMBINAAN OLAHRAGA USIA DINI SEKOLAH SEPAKBOLA (SSB) GADJAH MADA (GAMA) YOGYAKARTA - Nugroho Susanto; Alimuddin Alimuddin; Donal Syafrianto (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
The purpose of this study was to analyze the management of Gajah Mada Football School (SSA) Yogyakarta early childhood sports training. This type of research is a qualitative descriptive study, data collection by interview, observation and documentation study. Subjects in this study include: SSB student members (3 people), trainers (3 people), administrators (3 people) and athlete's parents (3 people) SSB GAMA Yogyakarta. The results showed that the GAMA football school which was used as a place to collect management data for early childhood sports training at a football school was well managed. Early childhood sports development at the Gama Yogyakarta soccer school has implemented five management functions in sports. The five management functions include planning, organizing, actuating, controlling and budgeting. The results of this study are expected to bring many changes in various ways, both from the community and the environment, especially those relating to the management problems of early age sports coaching that is in giving attention and handling to early childhood sports coaching, it is expected that other sports branches can develop early age sports coaching in accordance with sport management principles